Expert MySQL - Charles A Bell (Expert's voice in open source., 2007)
Since the enormous number of new features made available with MySQL release 5.0, MySQL has been gaining steam as a viable alternative to database behemoths like Oracle and IBM DB2. MySQL users now have the ability to extend MySQL with new SQL commands, optimize query execution, and embed MySQL within low-resource environments like embedded devices and kiosks.